Respiratory morbidity, healthcare resource use, and cost burden associated with extremely preterm birth in The Netherlands. (1st January 2021) - Houben, Eline; Siffel, Csaba; Overbeek, Jetty; Penning-van Beest, Fernie; Niklas, Victoria; Sarda, Sujata P.
Abstract: Background: Extremely preterm (EP) infants have high rates of respiratory morbidity and correspondingly high healthcare resource utilization. Objectives: Data from the PHARMO Perinatal Research Network were analyzed to quantify the burden of EP birth in the Netherlands. Methods: A retrospective analysis included infants <28 weeks gestational age with a birth record in the Perinatal Registry (1999–2015) and data in the PHARMO Database Network. Outcomes of interest included select comorbidities, hospital readmissions, and costs of hospitalization and medication up to 1- and 2-years corrected age. Outcomes were stratified by birth period (1999–2005, 2000–2009, 2010–2015) and by diagnosis of bronchopulmonary dysplasia (BPD) and chronic lung disease (CLD). Results: The cohort included 168 EP infants (37 born 1999–2005, 51 born 2006–2009, 80 born 2010–2015). Median (Q1–Q3) birth weights decreased by birth period from 970 (840–1, 035) g in 1999–2005 to 853 (695–983) g in 2010–2015. Overall, BPD and CLD were reported during the birth hospitalization in 40% and 29% of infants, respectively; rates of BPD increased and rates of CLD decreased by birth period. Eighty-four percent of EP infants had an additional comorbidity. Mean (standard deviation) costs of birth hospitalization were €110, 600 (€73, 000) for 1999–2005, €119, 350 (€60, 650) for 2006–2009, and €138, 800 (€130, 100) for 2010–2015. Birth hospitalization and total costs for up to 1- and 2-years corrected age were higher for infants with BPD and/or CLD than for those without either complication. Conclusion: Healthcare resource utilization and costs for EP infants, especially for those with respiratory morbidities, increased between 1999 and 2015. Future cost-effectiveness analyses are essential to determine the economic impact of this change and underscore the need for new therapeutic interventions to decrease clinical sequelae in this vulnerable population.